Development of a Quizizz-Based Mathematics Learning Assessment Tools to Improve Students' Concepts Understanding - Septi Wulandari; Haninda Bharata; Undang Rosidin (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to develop a Quizziz-based assessment tool and test its effectiveness on students' conceptual understanding abilities. This research began with preliminary studies, preparation of Quizziz-based Assessment Tools, validation of Quizziz-based Assessment Tools, limited field trials, and field trials. The subjects of this study were class VIII students of SMPN 6 Kota Metro in the 2022/2023 academic year. Research data was obtained through tests of critical thinking skills. The preliminary study results show the need to develop a Quizziz-based Assessment Tool. The Quizziz-based Assessment Toolkit is prepared by compiling a draft of the Quizziz-based Assessment Toolkit and all of its components. The results of the validation show that the Quizziz-based Assessment Tool meets the eligibility standards for content, media, and language in the proper category. The results of the field tests showed that there were differences in the conceptual understanding abilities of students in the experimental class and the control class. The conceptual understanding abilities of students who used Quizziz-based Assessment Tools were higher than the students' conceptual understanding abilities who did not use Quizziz-based Assessment Tools. Based on the field test results, it can be concluded that the Quizziz-based Assessment Tool effectively increases students' conceptual understanding skills.